2021
DOI: 10.3389/fimmu.2021.679556
|View full text |Cite
|
Sign up to set email alerts
|

When the Good Syndrome Goes Bad: A Systematic Literature Review

Abstract: BackgroundGood syndrome is a rare adult-onset immunodeficiency characterized by thymoma and hypogammaglobulinemia. Its clinical manifestations are highly heterogeneous, ranging from various infections to autoimmunity.ObjectiveThis study was to summarize patient characteristics, identify prognostic factors and define clinical subgroups of Good syndrome.MethodsA systematic literature review was conducted to include patients with Good syndrome identified in PubMed, Embase and Cochrane databases between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(80 citation statements)
references
References 133 publications
(33 reference statements)
1
57
1
Order By: Relevance
“…Only 6-10% of patients with thymoma develop GS and no specific histopathological subtype has been associated with the syndrome [2] . As in the case we report, hypogammaglobulinaemia does not always improve after thymectomy, indicating thymoma management alone is not sufficient to resolve this disorder [1] . Other therapeutic strategies are mainly supportive with antimicrobials and Ig replacement, recommended in GS patients who present with recurrent infections [2] .…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…Only 6-10% of patients with thymoma develop GS and no specific histopathological subtype has been associated with the syndrome [2] . As in the case we report, hypogammaglobulinaemia does not always improve after thymectomy, indicating thymoma management alone is not sufficient to resolve this disorder [1] . Other therapeutic strategies are mainly supportive with antimicrobials and Ig replacement, recommended in GS patients who present with recurrent infections [2] .…”
Section: Discussionmentioning
confidence: 41%
“…GS is a rare adult-onset combined immunodeficiency characterized by thymoma and hypogammaglobulinaemia [1] . Most cases occur between the ages of 40 and 70, with equal distribution between the sexes [2] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It then became apparent that this syndrome included reduced or absent mature B cells ( 3 ). In the latest review of GS, four cohort studies reported a total of 44% of individuals who had complete absence of peripheral B cells, while 50% had low levels ( 4 ). Thus, it is appropriate that reduced or absent B cells be accepted as an additional diagnostic criterion for GS ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%